Diseño de un algoritmo que evalúe la calidad de vapor inyectado en el sector sur del campo teca a partir de la herramienta de monitoreo distribuido de temperatura (DTS) (2017)
This project has as principal objective to design an algorithm that is able to quantify one of the most important properties in an injection process that is the steam quality at any point of the process; Because if the company has a continuous monitoring of that variable, decisions can be taken to mitigate the factors that affect it and improve the results of the recovery process. The purpose of this project is to develop an algorithm that calculates the steam quality that is being injected into three wells located in the South Sector of the Teca Field, allowing that the company Asesoría en Ingeniería de Petróleos S.A.S, deliver besides of injection profiles, an analysis from the behavior of the steam quality that is being injected by the companies that operate the field. For the algorithm development, the authors studied the temperature profiles at the time of injection from three injectors wells located in the field obtained by the distributed temperature sensing tool (DTS); and the calculated values were validated in the Geographix Software. With the algorithm results the company can give some recommendations to the company that operate the Teca Field, about the process of thermal recovery by steam injection that is taking place in there.